Provozní náklady Pražského hradu v roce 1538. Analýza pramene k dějinám financí v době Ferdinanda I. / Operating expenses of Prague Castle in year 1538. Source analysis of the history of finance at the time of Ferdinand I - Jiří Chmelař (Historie - Otázky - Problémy, 2015)
The document contains a summary of salaries and commissions for some officials and servants of Ferdinand I in 1538. It is divided into several parts — clergy and other staff at the Prague Castle, staff of the Chamber Court, the Bohemian Chamber and its officials and servants, servants of the Prague Castle, Prague Ungelt, and others.